The Means and the End - William O. Douglas (Washington University Law Quarterly, 1959)
The theory that the end justifies the means is an old one in the police state. It often lies hidden in ponderous law books or in obscure decisions. Frequently, however, it breaks through into news that all can understand.
Keywords: Urban transportation -- Federal aid; Criminal procedure; Soviet Union